Fallen city - Young, Adrienne, 1985- (Saturday Books, 2025)
In the ancient walled city of Isara, rebellion brews as politics, faith, and forbidden love collide. Luca Matius, a young legionnaire destined for power, and Maris Casperia, the daughter of a Magistrate and apprentice to a Priestess of stolen magic, are drawn together by fate. When a deadly secret ignites a holy war, their bond turns them into symbols on opposing sides of a divine struggle. Swept into a web of prophecy and rebellion, Luca and Maris must decide whether love or destiny will shape the future of their world.